Svartberget data 2020-12-16 ... - Laudon, Hjalmar; Nilsson, Mats; Peichl, Matthias; Erefur, Charlotta (https://b2share.eudat.eu, 2020)
Collection of data from the Svartberget research station in Vindeln, Northern Sweden. Both sets of data contain READMEs with further details on the contents of each file. ...